The development and construct validation of a Spanish version of an academic self-concept scale for middle school Hispanic students from families of low socioeconomic levels. - Michael, William B.; Rueda, Robert; Menjares, Pete C. (The Spanish Journal of Psychology, 2000)
Sin resumen